Isolamento e purificação parcial de L-asparaginase produzida por actinobactéria em solo do cerrado - Ferreira Neto, Petain Jose (2015)
The Cerrado is the second largest biome in Brazil. Such an environment has a different soil several other regions. There are various living beings in this biome, among them, the actinobacteria. They are microorganisms whose cell wall Gram-positive, >50% G+C (guanine + cytosine) in its DNA, produce substances with high economic value. Actinobacteria are major producers of enzymes useful to humans. L-asparaginase enzyme is used in acute limphoblastic leukemias therapy (ALL) also being used in the pre-treatment of foods rich in reducing sugars, inhibiting the formation of acrylamide. The aim of this study was to produce L-asparaginase enzyme isolated from a soil actinobacteria, characterize the enzyme and identify the species of bacteria isolated. A soil sample from Cerrado was collected and submited to a pretreatment. Chemotaxis of Actinoplanetes spores used for the selection of this organism. Nineteen morphspecies were recovered. We used a medium inducing L-asparaginase, and the pink halo around the colony measured. Isolated BC-A.1 produced the largest halo in less time, with an average enzyme content of 4.1. After the completion of the production steps, partial purification and optimization of enzymatic activity, it was realized that the enzyme produced by isolated morphospecies is very efficient at 40 ° C and pH 8.0. Biochemical, physiological and molecular tests were performed, and the observation with optical microscopy and scanning electron microscopy, but it was not possible to identify the species isolated, probably belongs to the genus Streptomyces.